Measurement of the fluctuations in the number of muons in extensive Air showers with the Pierre Auger Observatory - Freire, M. M. (2021)
Fil: Fil: Freire, M. M. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física de Rosario (IFIR-CONICET). Argentina.